2017
DOI: 10.1051/0004-6361/201731103
|View full text |Cite
|
Sign up to set email alerts
|

The Gaia-ESO Survey and CSI 2264: Substructures, disks, and sequential star formation in the young open cluster NGC 2264

Abstract: Context. Reconstructing the structure and history of young clusters is pivotal to understanding the mechanisms and timescales of early stellar evolution and planet formation. Recent studies suggest that star clusters often exhibit a hierarchical structure, possibly resulting from several star formation episodes occurring sequentially rather than a monolithic cloud collapse. Aims. We aim to explore the structure of the open cluster and star-forming region NGC 2264 ("3 Myr), which is one of the youngest, richest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 122 publications
(198 reference statements)
5
32
0
Order By: Relevance
“…In Fig. 11 we compare the Teff derived by Lanzafame et al (2015) (used by Venuti et al (2018)) to the Teff calculated from the given spectral type. Lanzafame et al (2015) derive Teff by fitting a series of broadened and vieled template spectra to their target spectra.…”
Section: Properties Of Confirmed Brown Dwarfsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Fig. 11 we compare the Teff derived by Lanzafame et al (2015) (used by Venuti et al (2018)) to the Teff calculated from the given spectral type. Lanzafame et al (2015) derive Teff by fitting a series of broadened and vieled template spectra to their target spectra.…”
Section: Properties Of Confirmed Brown Dwarfsmentioning
confidence: 99%
“…In Fig. 10 we show the HR diagram, with absolute J-band magnitude plotted against effective temperature (Teff), for the 32 young sources identified in this study, as well as the Venuti et al (2018) sample of spectroscopically confirmed cluster members. Isochrones for 0.5, 3, 5 and 10 Myr are plotted in black, evolutionary tracks for 1 ⊙ , 0.5 ⊙ , 0.075 ⊙ and 0.02 ⊙ in grey (Baraffe et al 2015).…”
Section: Properties Of Confirmed Brown Dwarfsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, The structure in the right of the cluster is so, because of the positive direction and the value of the vector sum being about 199.71 ± 2.33 mas/yr. Furthermore, NGC 2264, a young star cluster, also has been widely studied by Venuti et al (2018); Orcajo et al (2019); Buckner et al (2020); Nony et al (2021). Figure 7 displays the vector diagrams of members of NGC 2264 in the twodimensional system.…”
Section: The Prediction Of Changes In Star Cluster Morphologymentioning
confidence: 99%